Institutions and Their Role in Reduction of Uncertainty on the Market for Child Care - Вера Валериевна Галиндабаева (Journal of Economic Sociology, 2010)
The paper considers an issue of institutionalization of the market for individual services of child care. In Russia the state does not regulate this service market and does not impose specific formal institutions here. However, consumers tend to adopt the public institution of licensing: employers ask a given candidate for their job vacancy to provide a diploma or the other credentials confirmed by the state. Recruitment agencies imitate these institutional arrangements from the public sector of kindergartens. Attracting G. Akerlof’s conception and the P. DiMaggio and W. Powell’s theory of institutional isomorphism the author tries to explain how formal institutions are borrowed.няни